Evaluation of the New Centers for Disease Control and Prevention Ventilator-Associated Event Module and Criteria in Critically Ill Children in Greece. (11th July 2016) - Iosifidis, Elias; Chochliourou, Elpis; Violaki, Asimenia; Chorafa, Elisavet; Psachna, Stavroula; Roumpou, Afroditi; Sdougka, Maria; Roilides, Emmanuel
Abstract : OBJECTIVE: To evaluate the new adult Centers for Disease Control and Prevention (CDC) ventilator-associated event (VAE) module in critically ill children and compare with the traditionally used CDC definition for ventilator-associated pneumonia (VAP). DESIGN: Retrospective observational study of mechanically ventilated children in a pediatric intensive care unit in Greece January 1-December 31, 2011. METHODS: Assessment of new adult CDC VAE module including 3 definition tiers: ventilator-associated condition (VAC), infection-related VAC, and possible/probable ventilator-associated pneumonia (VAE-VAP); comparison with traditional CDC criteria for clinically defined pneumonia in mechanically ventilated children (PNEU-VAP). We recorded Pediatric Risk of Mortality score at admission (PRISM III), number of ventilator-days, and outcome. RESULTS: Among 119 patients with mechanical ventilation (median [range] number of ventilator-days, 7 [1–183]), 19 patients experienced VAC. Criteria for VAE-VAP were fulfilled in 12 of 19 patients with VAC (63%). Children with either VAC or VAE-VAP were on ventilation more days than patients without these conditions (16.5 vs 5 d, P=. 0006 and 18 vs 5 d, P<. 001, respectively), whereas PRISM-III score was similar between them. Mortality was significant higher in patients with new VAE-VAP definition (50%), but not in patients with VAC (31.6%), than the patients without new VAE-VAP (14%, P=. 007) or VAC (15%, P=. 1), respectively. No significant association was found between PNEU-VAP and death. Incidences of PNEU-VAP and VAE-VAP were similar, but the agreement was poor. CONCLUSIONS: VAE-VAP and PNEU-VAP found similar prevalence in critically ill children but with poor agreement. However, excess of death was significantly associated only with VAE-VAP. Infect Control Hosp Epidemiol 2016:1–5